Reflection on the Objective of Physical Education Department from Lecturers Point of View Physical Education Department at Sultan Qaboos University - السناني، يسرى بنت جمعة (رابطة التربويين العرب, 2019)
يهدف هذا البحث إلى التأمل من مدى تحقق أهداف التربية الرياضية الخاصة بقسم التربية الرياضية من وجهة نظر أعضاء هيئة التدريس بجامعة السلطان قابوس بسلطنة عمان. وذلك للتأكد من تحقق أعلى مستوى لهذه الأهداف وبالتالي أداء عالي للمعلمين من مخرجات هذا القسم. تعتبر آلية تقيم والتفكير في الأهداف من أهم الوسائل لتقييم فعالية برنامج من البرامج وبالأخص في التربية الرياضية. حيث تم معرفة آراء أعضاء هيئة التدريس في أهداف قسم التربية الرياضية كونهم مرتبطين بتحقيقها من خلال رؤية برنامج التربية الرياضية ككل وأيضاً كممارسين لتطبيق هذه الأهداف. وقد استخدمت الباحثة المنهج الوصفي باستخدام أداتي الاستبيان والمقابلة مع أعضاء هيئة التدريس في قسم التربية الرياضية بكلية التربية جامعة السلطان قابوس. وكان من أهم النتائج أن هناك اتفاق في الرأي بين أعضاء هيئة التدريس حول أهمية إعادة وضع الأهداف الخاصة بالبرنامج لتحقيق مستوى مخرجات عالي كون الجامعة هي المؤسسة التعليمية الحكومية الوحيدة في سلطنة عمان.
Reflection on Objective is a key component of educational research to develop and utilized for programmer in order to reach high implantation of the goals sit. This paper deals with reflection of the Physical Education Department Objectives (PEDO) from the views of the lecturers at Sultan. Qaboos University, by persons related to the department such as lecturers. Questionnaires were used to investigation method, and participants were asked to answer questions related to the aspects of the PEDO. Conducting interviews with the lecturer who also subjects taking the questionnaire could have illuminated many of their views on certain issues concerning the physical education department they were asked to reflect on. Views to various modifications in the PEDO were also brought and results were manly pro-reform except with lecturers. Moreover, the lecturers were all foreign, not Omani females. The major limitation though was that the study only focused on one educational institute in Oman.
Keywords: التربية الرياضية -- أعضاء هيئة التدريس -- الجامعات العمانية -- البرامج التدريبية